N.W.V. Castle at Newtown 17. Sept. 92. Co. Meath - Cocking, Thomas, fl. ca. 1783-1791 (1792)
View of the ruins of what is not "Newtown Castle" but the Hospital of St. John the Baptist or Crutched Friary, beside St. Peter's Bridge which spans the Boyne River, near Trim, County Meath, Ireland.
Inscribed in ink on verso: Castle of Newtown N:W: Co:y Meath. Sepr. 17th: 1792 / Reduced.
Inscribed in pencil on verso: Castle of Newtown, Co. Meath.
Inscribed in pencil u.l.: N.W. Castle at Newtown.
Title inscribed in ink u.c..
Watermark visible l.c..
Irish Topographical Prints & Drawings / Rosalind M. Elmes. - Malton Press, Dublin, 1975
Keywords: Crutched Friary (Meath, Ireland) -- 1790-1800.; St. Peter's Bridge (Meath, Ireland) -- 1790-1800.; Bridges -- Ireland -- Trim -- 1790-1800.; Hospitals -- Ireland -- Trim -- 1790-1800.; Religious dwellings -- Ireland -- Trim -- 1790-1800.; Rivers -- Ireland -- Trim -- 1790-1800.; Boyne River (Ireland) -- 1790-1800.; Ink drawings -- Irish -- 1790-1800.; Wash drawings -- Irish -- 1790-1800.